PEMERATAAN PEMBANGUNAN SOSIAL EKONOMI ANTARA INDONESIA TIMUR – BARAT SEBAGAI UPAYA MEMPERERAT KEBHINEKAAN - Muhammad Rifa'at Adiakarti Farid (Instructional Development Journal, 2019)
This paper will examine the problem of regional disparity in Indonesia, which has been the problem of decentralization increasingly complex with high levels of poverty in the regions. At the end of this paper will also be discussed about the equitable distribution of economic and social development related to the impact of national security and diversity issues. If the problem of inequality continues to be left, the worst impact will be the release of regions that are actually resource-rich but there is no even development.Keyword: Equitable Development, decentralization, diversity Tulisan   ini   akan   mengkaji   masalah   kesenjangan   wilayah   di Indonesia  yang  selama  ini,  masalah  desentralisasi  semakin  kompleks dengan tingginya tingkat kemiskinan di daerah. Di akhir tulisan ini juga akan dibahas mengenai pemerataan pembangunan ekonomi dan sosial terkait dampaknya dengan ketahanan bangsa dan masalah kebhinekaan. Jika masalah kesenjangan terus dibiarkan, maka dampak terburuk akan lepasnya daerah yang sebenarnya kaya sumberdaya tetapi tidak terjadi pembangunan secara merata.Keyword : Pemerataan Pembangunan, desentralisasi, kebhinekaan